Geographical feature and method factors significantly influence the reliability of ecological source information transmission at multi-scale - Kai Li; Wei Wu; Shiqi Tian; Linjuan Li; Zhe Li; Yue Cao (Ecological Indicators)
Ecological networks play a crucial role in balancing conservation and development, with notable dependencies on spatial scale, particularly within specific scale ranges. However, there is limited research on the factors influencing the reliability of ecological source information transmission across multi-scales. To address this issue, we integrated a multi-scale analysis framework based on previous studies and examined landscape scales ranging from 102 to 105 km2 across four extents, utilizing a 30 m base resolution and six additional grain sizes. This study was conducted in two regions with distinct geographical features: the Yangtze River Delta Region (YRDR) and the Loess Plateau Region (LPR). We employed Morphological Spatial Pattern Analysis (MSPA) and Comprehensive Evaluation (CE) methods to identify ecological sources across different extents and grain sizes, while analyzing the influence of various factors on information transmission. Key findings include: (1) At the landscape level, among all factors, including extents and grain sizes, the influence of geographical features on ecological source information transmission is significant, and it is greater than that of the methods. (2) A comparison between plains and plateaus reveals significant differences in the changes of ecological source information, even exhibiting opposite characteristics. (3) Among the two methods used, the MSPA method demonstrates greater stability when the extent changes, while the CE method exhibits greater stability when the grain size changes. Additionally, the results obtained by applying constraints at different scales are more stable than those without such constraints. This study reveals the mechanisms of ecological source information transmission across scales, underscoring the necessity and urgency of further research within different scale ranges. It also emphasizes that accurately identifying ecological sources is essential for determining critical biodiversity conservation areas and guiding decision-makers in formulating effective conservation strategies and land-use planning.